Granulocyte Colony-Stimulating Factor in Amniotic Fluid - Raynor, B. Denise (Hindawi Publishing Corporation, 1995)
Objective: The purpose of this study was to determine if granulocyte colony-stimulating factor (G-CSF) is normally present in amniotic fluid and then to determine if amniotic-fluid G-CSF levels are affected by labor and intrauterine infection. Methods: Amniotic fluid was collected from 35 patients in 4 groups: no labor, early labor, late labor, and labor plus chorioamnionitis. G-CSF levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: The mean amniotic-fluid G-CSF concentrations prior to labor were lower than during labor (0.49 ± 0.25 ng/ml for prior to labor vs. 1.83 ± 1.0 ng/ml for labor, P < 0.001). With chorioamnionitis, the mean levels were elevated compared with normal labor (25.0 ± 4.8 ng/ml for chorioamnionitis vs. 1.83 ± 1.0 ng/ml for normal labor, P < 0.0001). In early and late labor, G-CSF was higher than prior to labor (0.49 ± 0.25 ng/ml for no labor vs. 1.48 ± 1.0 ng/ml for early labor, P < 0.02, vs. 2.2 ± 0.8 ng/ml for late labor, P < 0.0005). The mean concentrations in early and late labor were not different. Conclusions: G-CSF is present in amniotic fluid and increased with labor. When labor is complicated by chorioamnionitis, G-CSF is significantly elevated.